PROFILE OF SELF-DISCLOSURE TENDENCY AMONG INSTAGRAM SECOND ACCOUNT USERS IN COLLEGE STUDENTS - Salma Nur Maulida; Rina Nurhudi Ramdhani (Universitas Pendidikan Indonesia, 2024)
Humans are inherently social beings who seek interaction with others. One way to establish connections is through self-disclosure, which involves revealing personal information to others. Social media platforms like Instagram have become popular spaces for building relationships and enhancing interpersonal communication. This study aims to explore the self-disclosure tendencies of early adult Instagram users with secondary accounts, focusing primarily on students. This research employs quantitative methods to provide a systematic, factual, and accurate description of the phenomenon. Findings indicate that self-disclosure patterns among student respondents are generally consistent and relatively high. The study offers deeper insights into how individuals reveal themselves in interpersonal settings, showing a tendency to share positive information, maintain honesty, and be accurate in their disclosures. Additionally, the results highlight the importance of considering gender differences in self-disclosure research, as women tend to be more open in sharing than men.